Development of a time projection chamber with a sheet-resistor field cage. (9th June 2019) - Miuchi, Kentaro; Ikeda, Tomonori; Ishiura, Hirohisa; Nakamura, Kiseki D; Takada, Atsushi; Homma, Yasuhiro; Abe, Ko; Ichimura, Koichi; Ito, Hiroshi; Kobayashi, Kazuyoshi; Nakamura, Takuma; Ueno, Ryuichi; et al.
Abstract: A new-concept time projection chamber (TPC) using a commercial resistive sheet, sheet-resistor micro-TPC (SRμ -TPC), has been developed and its performance measured. SRμ -TPC has the potential to create a more uniform electric field than conventional TPCs with resistor chains owing to its continuous sheet resistivity, and its production would be easier than that of conventional TPCs. The material used in this study, Achilles-Vynilas, was found to be thin, transparent, and have low radioactivity. A performance test with cosmic muons showed very promising results, including the demonstration of good tracking performance. This type of TPC field cage can offer an alternative for the widely used conventional field cages.